Ghrelin signalling in β‐cells regulates insulin secretion and blood glucose. Issue 1 (September 2014) - Yada, T.; Damdindorj, B.; Rita, R. S.; Kurashina, T.; Ando, A.; Taguchi, M.; Koizumi, M.; Sone, H.; Nakata, M.; Kakei, M.; Dezaki, K.
<x xml:space="preserve">Abstract</x> Insulin secretion from pancreatic islet β‐cells is stimulated by glucose. Glucose‐induced insulin release is potentiated or suppressed by hormones and neural substances. Ghrelin, an acylated 28‐amino acid peptide, was isolated from the stomach in 1999 as the endogenous ligand for the growth hormone (GH) secretagogue‐receptor (GHS‐R). Circulating ghrelin is produced predominantly in the stomach and to a lesser extent in the intestine, pancreas and brain. Ghrelin, initially identified as a potent stimulator of GH release and feeding, has been shown to suppress glucose‐induced insulin release. This insulinostatic action is mediated by Gαi2 subtype of GTP‐binding proteins and delayed outward K+ (Kv) channels. Interestingly, ghrelin is produced in pancreatic islets. The ghrelin originating from islets restricts insulin release and thereby upwardly regulates the systemic glucose level. Furthermore, blockade or elimination of ghrelin enhances insulin release, which can ameliorate glucose intolerance in high‐fat diet fed mice and ob/ob mice. This review focuses on the insulinostatic action of ghrelin, its signal transduction mechanisms in islet β‐cells, ghrelin's status as an islet hormone, physiological roles of ghrelin in regulating systemic insulin levels and glycaemia, and therapeutic potential of the ghrelin‐GHS‐R system as the target to treat type 2 diabetes.